2008
DOI: 10.2135/cropsci2007.09.0532
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends of Variation in Italian Rice Germplasm over the Past Two Centuries Revealed by AFLP and SSR Markers

Abstract: The aim of this study was to characterize the Italian rice (Oryza sativa L.) gene pool, paying particular attention to its variation over time, to determine whether human activity can reduce genetic variability, and whether such a reduction actually occurred in Italian rice varieties. We analyzed 135 Italian rice accessions, representing genotypes either introduced from abroad or developed in Italy from 1880 to 2001, using two groups of molecular markers, amplified fragment length polymorphisms and simple sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
18
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 30 publications
8
18
1
Order By: Relevance
“…However, from 1970s to 2000s the trend of increase was 4.71% and 8.92% for year of releasewise and longevitywise varieties, respectively. The observed trends in the present study are in agreement with Mantegazza et al, [12], who have reported increase of genetic diversity of Italian rice cultivars between 1850 and 2001. The same trend has been reported also by Morin et al, [35].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, from 1970s to 2000s the trend of increase was 4.71% and 8.92% for year of releasewise and longevitywise varieties, respectively. The observed trends in the present study are in agreement with Mantegazza et al, [12], who have reported increase of genetic diversity of Italian rice cultivars between 1850 and 2001. The same trend has been reported also by Morin et al, [35].…”
Section: Resultssupporting
confidence: 93%
“…Estimation of genetic diversity in varieties released in different crops during the last century reveals no clear trends [10]. In rice, both decreased [11] as well as increased trend of diversity [12] has been reported.…”
Section: Introductionmentioning
confidence: 98%
“…This result indicates that the genetic erosion is not only quantitative as described in the earlier sections, but also qualitative, meaning that over the last 30 years, the genetic make-up of this crop in NECAMP has shifted. This result is also similar to other studies that indicated that plant breeding can generate a qualitative change in the genetic diversity of the crops (Donini et al 2000;Khlestkina et al 2004;XiuQiang et al 2007;Le Clerc et al 2005;Lu and Bernardo 2001;Mantegazza et al 2008). Indeed, our result supports the hypothesis proposed by Martínez-Castillo et al (2004) that the sac ib and mulicion landraces could be improved varieties or landraces introduced to the Yucatan peninsula (probably between 1970 and 1980), that has displaced the local varieties of lima bean.…”
Section: Genetic Differentiation Between the 2 Years Of Collectionsupporting
confidence: 92%
“…Similar results were reported for many other crops (Khlestkina et al 2004;Xiu-Qiang et al 2007;Le Clerc et al 2005;Mantegazza et al 2008). This genetic shift may be a consequence of the introduction of improved varieties or landraces of P. lunatus (Hernández and Delgado 1992).…”
Section: Implications For Conservationsupporting
confidence: 87%
See 1 more Smart Citation